PROBLEMS OF GEOLOGIC AND ECONOMIC ESTIMATION OF THE MAYSKE AND KLYNTSIVSKE GOLD DEPOSITS OF THE UKRAINIAN SHIELD - CHAIKA, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The data on geologic and economic estimation of the Mayske and Klyntsivske gold deposits is given. General features of the structure, substance composition of the rocks and ore mineralization are analyzed. Detailed exploration of the abovementioned objects is described. The problems of geologic and economic estimation and possible ways of their solution are discussed.